PRODUCT QUALITY, PRICE, AND TRUST TO INCREASE CUSTOMER SATISFACTION AT TERRACE CAFÉ PARK HOTEL - Sulistyo Haryono (Journal of Management and Leadership, 2022)
The study aims to determine product quality, price, and trust in customer satisfaction at Terrace Café Park Hotel Jakarta. The data collection method in this study was conducted by survey method by distributing questionnaires that have been tested for validity and reliability to consumers who enjoy food at Terrace Café Hotel Park Jakarta. The sample withdrawal technique uses the purposive sampling technique. Respondents selected as a sample were consumers who at least twice enjoyed food at Terrace Cae Hotel Park Jakarta. The number of eligible samples was 170 questionnaires. Data processing is done using the Smart PLS application version 3. 2.9. Using significance the results showed that the quality of the product had a positive and significant impact on customer satisfaction. Price and trust also have a positive and significant effect on customer satisfaction.